Modified Efficient and Simple Method for Biological Spill Cleanup. (September 2019) - Vijayan, Viji; Sern, Benson Ng Beng; Johnson, Barbara
Introduction: Spill response procedures are an important aspect of laboratories where infectious materials are handled. The decades-old conventional method of spill cleanup uses paper towels to cover the spill. It requires 2 staff and involves a considerable amount of bending and squatting and being able to balance in those positions while wearing personal protective equipment (PPE). In this article, we describe a method that simplifies spill cleanup and compares it to the conventional method. The simplified method can be easily conducted by 1 person, takes about half the time, generates less waste, and reduces the amount of time spent in contaminated areas. Objective: The objective is to describe a modified, simple method of spill cleanup. Methods: A mock spill was created and a spill response initiated per the institution's procedure. The simplified procedure uses a pail filled with decontaminant and a household mop dripping with the decontaminant. Mopping is done from the noncontaminated area toward the contaminated area so the spill does not spread. Mopping is done more than once, and all the materials used, including the mop(s), are disposed as biohazardous material. Results: The simplified spill cleanup process described here can be performed by just one person and does not require bending and squatting while wearing PPE. The kit is very simple, consisting of a pail and a mop, which are common household tools familiar to most people. Conclusion: The mop-and-pail methodology is simple, requires only one staff member, generates less biological waste, and requires less training and practice while effectively cleaning the spill.